Facteurs affectant l'adoption des cultures fourragères dans les élevages laitiers péri-urbains de Bobo-Dioulasso, Burkina Faso - Abdoulaye, AT.; Kamuanga, M.; Hamadou, S.; Lowenberg-Deboer, J. (Tropicultura, 2005)
Factors Affecting the Adoption of Fodder Crops in Bobo-Dioulasso (Burkina Faso) Peri-urban Dairy Farms. The study aims to identify the factors affecting the adoption of annual (Dolichos lablab) and perennial (Andropogon gayanus, Brachiaria ruziziensis and Panicum maximum) fodder crops on peri-urban dairy farms of Bobo-Dioulasso (Burkina Faso). The results of a logistic regression model (LIMDEP ©) revealed a number of significant factors (P< 0.05) associated with five main constraints preventing wider use of fodder crops in cultural practices. These include increased labor demand at peak cropping season, land tenure rights, field protection, availability of fodder seeds, and low productivity gain associated with the introduction of fodder crops. Fodder crops adoption rates would be higher with the adaptation of the technology to local conditions and increased emphasis on farmers' training and sensitization campaigns.